TEKNIK ENKAPSULASI ANTIOKSIDAN MELALUI PENGERINGAN SEMPROT - Pawestri, Setyaning; Syahbanu, Fathma (Agros Journal of Agriculture Science, 2024)
Most widely consumed agriculture products worldwide are vegetable and fruit-based products rich in bioactive compounds such as vitamins, polyphenols, and other antioxidants. These molecules are susceptible to oxidation and degradation during food processing, especially when exposed to heat. This review discusses the effects of encapsulation using spray drying on bioactive compounds and how encapsulation technology can be utilized to protect and optimize the functional properties of bioactive. Encapsulation can also aid the creation of desirable sensory attributes (e.g., aroma, texture, colour, and taste), thus playing an essential role in developing novel foods and beverages. Encapsulation has successfully preserved encapsulated bioactive compounds from external conditions while aiding the controlled release of transported active compounds. Among the various variations and applications of encapsulation, microencapsulation and nanoencapsulation of food bioactive is the main focus of this review, which discusses the principles related to technological developments as well as current applications so that the protective effects and bioavailability of bioactive components in food systems can be fulfilled. This manuscript review was conducted using the narrative literature review method. Keywords: antioxidant, bioactive compound, encapsulation, spray drying INTISARIProduk agrikultur yang paling banyak dikonsumsi di seluruh dunia adalah produk berbasis sayuran dan buah-buahan yang kaya akan senyawa bioaktif seperti vitamin, polifenol, dan antioksidan. Molekul-molekul ini sangat rentan terhadap oksidasi dan degradasi selama pemrosesan makanan, terutama akibat paparan suhu. Ulasan ini membahas efek enkapsulasi dengan pengeringan semprot pada senyawa bioaktif dan bagaimana teknologi enkapsulasi digunakan untuk melindungi dan mengoptimalkan sifat fungsional bioaktif makanan. Enkapsulasi juga dapat membantu menghasilkan atribut sensorik yang diinginkan (misalnya, aroma, tekstur, warna, dan rasa), sehingga memainkan peran penting dalam pengembangan produk baru. Enkapsulasi telah terbukti berhasil sebagai proses yang efektif untuk melindungi senyawa bioaktif yang dienkapsulasi dari kondisi eksternal, sekaligus membantu pelepasan terkontrol dari senyawa aktif yang diangkut. Di antara berbagai variasi dan aplikasi enkapsulasi, mikroenkapsuliasi dan nanoenkapsulasi bioaktif dari makanan adalah fokus utama dari ulasan ini yang membahas prinsip-prinsip terkait perkembangan teknologi serta aplikasi saat ini sehingga  efek perlindungan dan  bioavailabilitas dari komponen bioaktif dalam sistem pangan dapat terpenuhi. Ulasan naskah ini dilakukan dengan menggunakan metode literature review narrative. Kata Kunci: antioksidan, enkapsulasi, komponen bioaktif, pengeringan semprot